Trends in Sciences: Celebrating Record-High 2024 CiteScore - Channuie, Phongpichit (Trends in Sciences, 2025)
It is with great pride and enthusiasm that we announce a significant achievement for Trends in Sciences—the journal has reached a CiteScore of 1.8 in 2024, as released by Scopus on June 3, 2025. This remarkable increase from 1.2 in 2023 represents the highest CiteScore in the journal’s history, underscoring its rapid ascent and growing academic influence on both national and international stages. This upward trajectory in CiteScore is more than a numerical milestone; it is a clear indication of the journal’s expanding reach, scholarly relevance, and citation impact across multiple scientific fields. Most notably, Trends in Sciences now holds the top position among all multidisciplinary journals published in Thailand, a recognition that reflects the trust and esteem of our contributors, readers, reviewers, and editorial team. The continuous growth in CiteScore—from 0.8 in 2022, to 1.2 in 2023, and now 1.8 in 2024—illustrates the journal’s steadfast commitment to academic rigor, innovation, and quality. Each successive increase is the outcome of a collaborative ecosystem involving meticulous peer review, strong editorial oversight, and the publication of impactful research that addresses current scientific challenges. Our contributors have played a pivotal role in this success. We extend sincere appreciation to the authors who entrusted their research to Trends in Sciences and to the reviewers whose expertise ensures the publication of high-quality and credible scholarship. Furthermore, the support from the wider research community has been instrumental in elevating the journal’s visibility, reputation, and citation performance. This accomplishment also reflects our strategic direction: to become a leading international platform for publishing interdisciplinary and cross-cutting scientific research. As science continues to evolve beyond traditional disciplinary boundaries, Trends in Sciences is embracing this shift by welcoming submissions that integrate diverse fields and propose novel approaches to global and regional issues. Looking ahead, we aim to build upon this success by: Enhancing editorial efficiency to shorten review and publication cycles. Expanding international collaborations to diversify author contributions and editorial participation. Investing in digital innovations to increase accessibility, discoverability, and reader engagement. We are confident that these strategic initiatives will sustain our momentum and reinforce our position as a journal of choice for authors seeking broad impact and multidisciplinary dialogue. In conclusion, the 2024 CiteScore of 1.8 is more than a statistical achievement—it is a symbol of the journal’s maturation, global relevance, and the scientific community’s growing recognition of our work. We remain dedicated to advancing knowledge, fostering inclusive academic discourse, and contributing meaningfully to the progress of science and society. We thank you for being part of this journey and invite you to continue contributing to and supporting Trends in Sciences as we move forward together.